IBM Storage Networking SAN512B-6 and SAN256B-6 Directors - Gilge, Megan (IBM Corporation, International Technical Support Organization, 2018)
This IBM® Redbooks® product guide describes the IBM Storage Networking SAN512B-6 (8961-F08) and SAN256B-6 (8961-F04) directors and the IBM b-type Gen 6 Extension Blade (FC 3892, 3893). Digital transformation is pushing mission-critical storage environments to the limit, with users expecting data to be accessible from anywhere, at any time, on any device. Faced with exponential data growth, the network must evolve to enable businesses to thrive in this new era. A new approach to storage networking is needed to enable databases, virtual servers, desktops, and critical applications, and to unlock the full capabilities of flash. By treating the network as a strategic part of a storage environment, organizations can maximize their productivity and efficiency even as they rapidly scale their environments. IBM Storage Networking SAN512B-6 and SAN256B-6 directors with Fabric Vision technology are modular building blocks that combine innovative hardware, software, and built-in instrumentation to ensure high levels of operational stability and redefine application performance. Fabric Vision technology enhances visibility into the health of storage environments, delivering greater control and insight to quickly identify problems and achieve critical service level agreements (SLAs). Breakthrough 32 Gbps performance shatters application performance barriers and provides support for more than 1 billion input/output operations per second (IOPS) for flash-based storage workloads while 128 Gbps UltraScale inter-chassis links enable simplified, high-bandwidth scalability between directors.